Canada's Postwar Balance of Payments Adjustments: A Different View - Jr., Ernest W. Ogram (The Review of Economics and Statistics, 1961)
HE purpose of this paper is to consider T Canada's mechanism of international adjustment from I946 through I957. Canadian loans and export credits amounted to approximately $2 billion during this period. The classical writers, i.e., Ricardo and Mill, as well as the modern Keynesians, primarily Metzler and Machlup, state that when a nation is involved in long-term lending, the capital account is the independent variable and as such induces equilibrating changes in the current account.' The two schools differ, however, with respect to the mechanism of adjustment. The classical writers claim that adjustment occurs through changes in prices and factor allocations, whereas the latter group claim that adjustment takes place through changes in purchasing power. The thesis offered here, however, is that the adjustment process from this capital outflow can be explained conceptually by a system of mutually interdependent equations. The paper is divided into three parts. The first outlines the adjustment process, utilizing simultaneous equations for two periods, I94650 and I95I-57, using a three dimensional model, the analysis of which is not amenable to geometrical presentation.2 Then an attempt is made to verify statistically the hypothesis presented in the model. The last section deals with the application of the model for balance of payments analysis. Adjustment Process Under the Simultaneous Equations Approach